The Development of Nervous Problem Based Modulewith Character Conservation for Nervous System Materials in the Senior High School - Qudsiya, Reefa; Lisdiana, Lisdiana; WH, Nugrahaningsih (Journal of Biology Education, 2018)
Nervous system teaching materials available in schools do not contain scientific-related content as mandated by the 2013 curriculum. In addition, teaching materials also do not contain student character reinforcement content. The purpose of this study is to develop “Nervous Problem Based Module with a  Conservation Character” as a nervous system learning supplement. This type of research is Research and Development (R&D) using ten steps, namely identification of potential and problems, data collection, product design, product design validation, product design revisions, small scale trials, product revision I, large scale trials, product revision II, and final products. The research subjects were students of class XI of SMA N 1 Bae Kudus. Nervous Problem Based Module with a  Conservation Character  tested the feasibility, readability, and effectiveness. Feasibility tests obtained very valid results. Readability test results were very valid. Test effectiveness by applying  Nervous Problem Based Module with a  Conservation Character in learning, obtained effective results and can be used in learning. The insertion of the conservation character reinforcement in the module gives positive results on the character of students. It can be concluded that “Nervous Problem Based Module with a Conservation Character” is decent and effectively applied in the nervous system learning.